Pembelajaran Kontekstual dan Pembelajaran Based Learning - Mortalisa, Tara Putri; Ismail, Fajri; Afgani, Muhammad Win (Peneliti.net, 2025)
This research aims to analyze contextual learning and problem-based learning. This research includes qualitative research. The approach used is purely library research. Data is obtained from reading materials obtained by researchers from books, articles contained in print. The data were collected and sorted to fill in the answers to the formulated research questions. The analysis used a content analysis approach to obtain information related to contextual learning and problem-based learning. The conclusion of this research is that contextual learning is a learning that relates everyday contexts to learning materials so that students are able to interpret the knowledge/skills they learn and can flexibly apply their knowledge/skills from one problem/context to another. The contextual approach involves seven main components of contextual learning, namely: constructivism, discovery, questioning, learning community, modeling, reflection, and authentic assessment. Problem-based learning is one of the appropriate models developed in technology learning to respond to issues of improving the quality of technology learning and anticipating changes that occur in the world of work. Characteristics and learning stages of the Problem-Based Learning model. Problem-based learning is developed primarily to help students develop thinking, problem-solving, and intellectual skills, learn about various adult roles by engaging in real or simulated experiences, and become autonomous and independent learners